Emotional Intelligence and Digital Competence in Enhancing Teacher Performance: A Two-Stage Higher-Order PLS-SEM with Learning Effectiveness as Mediator - Opi Vita Mayang Sari; Bambang Dwi Suseno; Umalihayati Umalihayati (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines how emotional intelligence and digital competence jointly influence teacher performance through the mediating role of learning effectiveness in private elementary schools in Cilegon, Indonesia. It addresses a key gap in prior research by adopting a process-oriented perspective to explain how teacher competencies are translated into professional performance. Methodology: A cross-sectional survey was conducted involving 243 teachers selected using proportional stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a two-stage higher-order approach to capture the multidimensional nature of the constructs and their structural relationships. Main Findings: The results indicate that emotional intelligence and digital competence both have significant positive effects on teacher performance. Emotional intelligence strongly predicts digital competence and contributes to learning effectiveness, while digital competence enhances instructional quality. Learning effectiveness partially mediates the relationships between competencies and performance, demonstrating that teacher capabilities influence outcomes both directly and through teaching–learning processes. Novelty/Originality of this study: This study contributes by proposing an integrative competency framework that positions emotional intelligence as a foundational resource for digital competence and identifies learning effectiveness as a key mediating mechanism. It extends existing models by offering a process-based explanation of how competencies translate into teacher performance, providing both theoretical advancement and practical insights for teacher development in the digital era.